Factors Affecting Stock Prices Using Moderation Variables in Coal Subsector Companies Listed on The Indonesian Stock Exchange 2015 - 2022 - Dinda Lestari; Devyanthi Syarif; Diah Febriyanti; Tjipto Sajekti; Dwi Sugiantoro (Universitas Indonesia Membangun, 2024)
The moderating variable in this study is firm size. The study aims to determine the effects of net profit margin, debt-to-debt equity ratio, and total asset turnover on stock prices. This study falls under the category of quantitative research and employs a descriptive and verification technique. Secondary data were used; the procedures for gathering the data were provided by documentation and a review of the literature. In the sampling process, purposeful sampling is employed. The data analysis techniques used in this study included modified regression analysis (MRA), coefficient of determination analysis, product-moment correlation coefficient analysis, multiple regression analysis, and the classical assumption test. According to the results of the simultaneous test (F test), the debt-to-equity ratio, net profit margin, and total asset turnover all influence stock prices concurrently. The correlation criterion table shows that the correlation score is between 41% and 60%, which indicates a moderate connection. This indicates that, beyond the variables analysed, there exist additional factors that have the potential to increase the share prices of mining companies in the coal subsector on the Indonesia Stock Exchange between 2015 and 2022.